Features of the emotional intelligence of athletes in individual and team sports - Sattorov, Mirshod (Физическое воспитание, спорт и здоровье, 2020)
The article examines the relevance of the development of emotional intelligence in the field of applied sports psychology, provides a comparative analysis of the features of the emotional intelligence of athletes in team and individual sports.